Histopathological Assessment of the Endoscopic Resection Specimen - Sterlacci, William; Vieth, Michael (Visceral Medicine, 2024)
Background: Endoscopic resection for early neoplastic lesions of the gastrointestinal tract is nowadays the accepted and feasible method also in non-tertiary reference centers. The main clinical advantage is the preserved quality of life compared to larger surgical procedures. Summary: Clinical colleagues need to have basic knowledge of factors that may influence the outcome of histopathology. This article discusses issues connected to the histopathological work-up of endoscopic resection specimens within in the gastrointestinal tract. Key Messages: Besides the clinical technical prerequisites, standardized histopathology is the key element of the pathology laboratory work-up of endoscopic resection specimens. Overdiagnoses of reactive lesions as low-grade neoplasia lead to incomparable study data and although criteria to overcome this situation exist, they are not accepted worldwide, calling for further efforts in harmonization.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Endoscopic resection; Issues; Pathology; Quality